2022
DOI: 10.3390/ani12212994
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and Animal Strategies to Reduce the Environmental Impact of Pastoral Dairy Systems Result in Altered Nutraceutical Profiles in Milk

Abstract: The objective of this study was to evaluate and provide further insights into how dairy cows genetically divergent for milk urea N breeding values [MUNBV, high (2.21 ± 0.21) vs. low (1.16 ± 0.21); µ ± SEM], consuming either fresh cut Plantain (Plantago lanceolata L., PL) or Ryegrass (Lolium perenne L., RG) herbage, impacted the nutraceutical profile of whole milk by investigating amino and fatty acid composition and applying metabolomic profiling techniques. Both diet and MUNBV, and their interaction term, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
1
3
0
Order By: Relevance
“…There were also small changes in branch‐chain and odd‐number carbon length fatty acids in milk fat reported by Mangwe et al (2018). Similar changes in milk fatty acids in response to feeding PL herbage have been reported by Marshall et al (2022b). Feeding PR‐red clover‐PL silage, with the latter at 35% inclusion in the stack, also resulted in a marked increase in the C18:3 fatty acid content of milk fat (>5‐fold relative to total mixed ration, TMR, Ineichen et al, 2019).…”
Section: Effects Of Feeding Plantain On Milk and Meat Compositionsupporting
confidence: 87%
See 2 more Smart Citations
“…There were also small changes in branch‐chain and odd‐number carbon length fatty acids in milk fat reported by Mangwe et al (2018). Similar changes in milk fatty acids in response to feeding PL herbage have been reported by Marshall et al (2022b). Feeding PR‐red clover‐PL silage, with the latter at 35% inclusion in the stack, also resulted in a marked increase in the C18:3 fatty acid content of milk fat (>5‐fold relative to total mixed ration, TMR, Ineichen et al, 2019).…”
Section: Effects Of Feeding Plantain On Milk and Meat Compositionsupporting
confidence: 87%
“…There was no impact of PL feeding on milk protein content apart from one report of a small increase which was associated with an increase in milk protein yield (Nkomboni et al, 2021). Marshall et al (2022b) also reported changes in multiple minor milk components (mostly intermediary metabolites) from cows fed PL vs. PR herbage.…”
Section: Effects Of Feeding Plantain On Milk and Meat Compositionmentioning
confidence: 98%
See 1 more Smart Citation
“…The question arises, are there ecological implications and connections between phytochemically diverse swards and the health of humans and soil (Provenza et al, 2019). If so, this expanded pool of nutrients, medicines, and prophylactics, known as plant secondary compounds, must be considered to understand the effects of consuming animal products on human health, as they have been reported to be concentrated in the meat and milk of livestock consuming those plants (Marshall et al, 2022;.…”
Section: Introductionmentioning
confidence: 99%